KERANCUAN PENATAAN HAM DALAM SISTEM HUKUM NASIONAL INDONESIA - Supriyanto - (Wacana Hukum, 2011)
AbstractDespite the attention of human rights has existed since long, but the struggle to get legal protection in state constitution looks after the birth of Magna Charta in England in 1215 which is followed by Declaration of Independence in the United States of America in 1776 and Declaration des droits de “I” home et du citoyen in France in 1780. In Indonesia this right has received legal protection in 1945 Constitution, RIS Constitution, or Temporary Constitution, and become much stronger after the birth of MPR Decree Number XVII year 1998 which is followed by Act Number 39 year 1999 on Human Rights, Act Number 26 year 2000 on Human Rights Court which is followed by Amendment of 1945 Constitution which govern specifically Human Rights Chapter in chapter X A which consist of 10 articles. Even though human rights in Indonesia have evolved considerably, but when we look further there is still many weaknesses which contradict one and another. For example: Article 281 Amendment of 1945 Constitution and Article 4 Act of Human Rights which adheres the principle of non retroactive absolutely with Article 43:1 Act of Human Rights Court and Explanation of Article 4 Human Rights Act which adheres the principle of retroactive for gross violation of human rights. Contradiction is also occurs in Article 4 Human Rights Act body and its explanation. Keywords: human rights.